Peran Analisis Diklat dalam Perencanaan Pelatihan di PPSDM Aparatur - Ani Maliani; Tris Sutrisno (Pusat Pengembangan Sumber Daya Manusia Aparatur, 2022)
Peran Jabatan Pelaksana Analis Diklat dalam perencanaan pelatihan sangatlah penting, mulai dari menganalisis hasil pelaksanaan diklat, penelaahan guna penyusunan rekomendasi bidang diklat, penyiapan konsep proposal program diklat, serta penyiapan rencana program diklat.Survey menunjukkan 61 % pegawai mengalami kesulitan dalam perencanaan diklat, hal ini membuktikan pelunya peningkatan peran analis diklat. Di lain sisi kompetensi dan jumlah funsional analisis diklat secara kuantitas dan kualitas masih harus ditingkatkan.Metode pengambilan data dalam perencanaan diklat masih sebatas survey; hasil analisis belum didukung hasil review kinerja individu dan organisasi. hal ini mengakibatkan perencanaan diklat dan kebutuhannya belum dirasakan optimal.Potensi dan peran analis diklat sangat penting namun seolah tidak terlihat perannya sejauh ini. Jabatan perencana kebutuhan diklat di PPSDM Aparatur tidak hanya di emban oleh seorang analis diklat, namun dapat diikuti oleh jenjang jabatan fungsional lain yaitu analis pengembangan kompetensi SDM Aparatur.Kata kunci : analis Diklat, perencanaan Diklat.AbstractThe role of the Training Analyst in training planning is very important, starting from analyzing the results of the education and training implementation, reviewing the preparation of recommendations for the education and training field, preparing the concept of the education and training program proposal, and preparing the training program plan.The survey shows that 61% of employees have difficulty planning their education and training programs; this proves the need to increase the role of the training analyst. On the other hand, the competency and the number of functional analyses of training in quantity and quality still need to be improved.The data collection method in the education and training planning is still limited to only surveys; individual and organizational performance reviews have not supported the analysis results. The limited survey has resulted in the planning of education and training, and its needs have not been felt optimally.The potential and role of the education and training analyst are very important, but its role seems to be invisible so far. The planning and training needed position at the PPSDM Apparatur is not only carried out by a training analyst. Still, it can be followed by other functional positions, namely a development competency analyst of the Aparatur human resources.Keywords : Training analyst, training planning.